The Development of Disease-Modifying Therapies for Osteoarthritis (DMOADs): The Evidence to Date - Oo WM; Little C; Duong V; Hunter DJ (Dove Medical Press, 2021)
Win Min Oo,1,2 Christopher Little,3 Vicky Duong,1 David J Hunter1 1Rheumatology Department, Royal North Shore Hospital, and Institute of Bone and Joint Research, Kolling Institute, Faculty of Medicine and Health, The University of Sydney, Sydney, Australia; 2Department of Physical Medicine and Rehabilitation, Mandalay General Hospital, University of Medicine, Mandalay, Mandalay, Myanmar; 3Raymond Purves Bone and Joint Research Laboratories, Institute of Bone and Joint Research, Kolling Institute, Faculty of Medicine and Health, The University of Sydney, Sydney, AustraliaCorrespondence: David J HunterRheumatology Department, Royal North Shore Hospital, and Institute of Bone and Joint Research, Kolling Institute, Faculty of Medicine and Health, The University of Sydney, Sydney, AustraliaEmail david.hunter@sydney.edu.auAbstract: Osteoarthritis (OA) is a complex heterogeneous articular disease with multiple joint tissue involvement of varying severity and no regulatory-agency-approved disease-modifying drugs (DMOADs). In this review, we discuss the reasons necessitating the development of DMOADs for OA management, the classifications of clinical phenotypes or molecular/mechanistic endotypes from the viewpoint of targeted drug discovery, and then summarize the efficacy and safety profile of a range of targeted drugs in Phase 2 and 3 clinical trials directed to cartilage-driven, bone-driven, and inflammation-driven endotypes. Finally, we briefly put forward the reasons for failures in OA clinical trials and possible steps to overcome these barriers.Keywords: osteoarthritis, DMOADs, disease-modifying drugs, intra-articular therapy, phenotype, endotype